Analisis Spasial Indeks Kekeringan di Daerah Bandar Lampung - Sigiro, Japen Husoran; Amin, M.; Ridwan, Ridwan; Rosadi, Bustomi (abe.fp.unila.ac.id, 2024)
Drought is a routine case of natural disasters. Drought in a region can disrupt human activities. Drought occurs due to reduced rainfall, temperatures that are too high than normal, low soil moisture and insufficient surface water supply. The aim of this research is to obtain the distribution of rain and analyze the drought value index in the Bandar Lampung area. The cause of this drought is a step to predict the drought that will occur by analyzing the rain and temperature. This analysis is done by calculating the water balance and determining the drought level using drought index table by thorthwaite mather. The drought analysis is conducted in Bandar Lampung area, where the Bandar Lampung area is the capital city of Lampung province with an area of ± 160 km2 with an average population density of 8,316 people/km2. From the Drought Value Index, the level of drought in the Bandar Lampung area is predominantly low and the level of drought is moderate in the Peace District area. Keywords: Drought, Spatial Analysis, Water Balance